A head to toe pediatric assessment - Jordan, Donna; American Journal of Nursing Company ([Carrolton, Tex.] : Westcott Communications, 1993)
(Producer) Thorough and methodical--cornerstones to remember when conducting a complete physical examination. However, when conducting the physical examination of a child, equally important are flexibility and patience. The nurse needs to be able to adjust the procedure to accommodate the child. This program describes, in detail, a complete physical assessment of a young child. Covered are: skin; head and neck; eyes, ears, and nose; mouth and oropharynx; chest and lungs; abdomen; musculoskeletal system; neurological system
Videocassette is available at Koleksi Media, Perpustakaan HUKM
Approved for 1 hr. CNE credit
Donna Jordan
Keywords: Nursing Assessment -- infant -- child; Pediatric Nursing -- methods; Physical Examination -- methods